Communication of emotion in home hospice cancer care: Implications for spouse caregiver depression into bereavement. Issue 5 (5th April 2019) - Reblin, Maija; Baucom, Brian R.W.; Clayton, Margaret F.; Utz, Rebecca; Caserta, Michael; Lund, Dale; Mooney, Kathi; Ellington, Lee
Abstract: Objective: Family caregivers of cancer hospice patients likely benefit from clinician provision of verbal support and from expression of positive emotions. Our aim was to identify the effects of hospice nurse supportive communication as well as caregiver‐nurse exchange of positive emotions on family caregiver depression during bereavement. Methods: This prospective, observational longitudinal study included hospice nurses (N = 58) and family caregivers of cancer patients (N = 101) recruited from 10 hospice agencies in the United States. Digitally recorded nurse home visit conversations were coded using Roter interaction analysis system to capture emotion‐focused caregiver‐nurse communication and supportive nurse responses. Caregivers completed the Hospital Anxiety and Depression Scale Anxiety Subscale and Geriatric Depression Scale‐Short Form at study enrollment and at 2, 6, and 12 months after patient death. Results: Caregivers had moderate levels of depression at study enrollment and throughout bereavement. Multilevel modeling revealed that caregiver positive emotion communication and nurse emotional response communication are associated with caregiver depression in bereavement. There was no significant association between caregiver distress communication and depression in bereavement. Conclusions: This is the first study to demonstrate that communication demonstrating emotional expression between cancer spouse caregivers and nurses during home hospice may have implications for caregiver depression up to a year after patient death. Our findings may help identify caregivers who may be coping well in the short term but may struggle more over time.